Corporate Governance, Islamic Social Reporting, Intensitas Aset Tetap, dan Agresivitas Pajak pada Bank Syariah - Amalia, Dita; Suryaputri, Rossje V. (E-Jurnal Akuntansi; Vol 33 No 2 (2023)DO - 10.24843/EJA.2023.v33.i02.p10, 2023)
The aim of this study is to empirically examine the effect of the proportion of independent commissioners, audit committees, Islamic Social Reporting (ISR) and fixed asset intensity on tax aggressiveness with bank size and profitability as control variables. The method used in this research is multiple linear regression analysis. The population in this study is Islamic banking registered with the OJK in 2016-2021. Sampling used purposive sampling method and obtained 49 observational samples. Tax aggressiveness is measured by the Effective Tax Rate (ETR). The results showed that the proportion of independent commissioners and audit committees had a negative effect on tax aggressiveness. Fixed asset intensity has a positive effect on tax aggressiveness. Research also proves that Islamic social reporting has no effect on tax aggressiveness. Keywords: Corporate Governance; Islamic Social Reporting; Fixed Asset Intensity; Tax Aggressiveness.